2005
DOI: 10.1063/1.1862244
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic functions of water and ice confined to 2nm radius pores

Abstract: The heat capacity C(p) of the liquid state of water confined to 2 nm radius pores in Vycor glass was measured by temperature modulation calorimetry in the temperature range of 253-360 K, with an accuracy of 0.5%. On nanoconfinement, C(p) of water increases, and the broad minimum in the C(p) against T plot shifts to higher temperature. The increase in the C(p) of water is attributed to an increase in the phonon and configurational contributions. The apparent heat capacity of the liquid and partially frozen stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 51 publications
4
73
0
1
Order By: Relevance
“…At such mesoscopic scale, numerous studies have shown that the structure and the physical properties of confined liquids in cavities differ strikingly from the bulk system [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The experiments on the confinement of water or associated liquid such as alcohol in mesoporous materials (aerogels, controlled pore glass, MCM-41.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…At such mesoscopic scale, numerous studies have shown that the structure and the physical properties of confined liquids in cavities differ strikingly from the bulk system [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The experiments on the confinement of water or associated liquid such as alcohol in mesoporous materials (aerogels, controlled pore glass, MCM-41.…”
Section: Resultsmentioning
confidence: 98%
“…Numerous investigations have been devoted on the understanding of confined water and other liquids into mesoporous materials such as MCM-41, Vycor, clay and porous silicon [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These studies have revealed effects of confinement which affect both the structure and dynamics of the confined system of which properties differ strictly from these-ones of bulk liquid [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Surfactant systems self assemble into a variety of structures which present particular organizations of the membranes and provide model system to host small or significant amounts of water for mimic confinement in biological objects [1,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of solid surfaces has been considered: silica pores (Vycor glass) [25,26], platinum [27], magnetite [28], zirconia [29], or pure carbon composites (graphite structure) in several geometries, from planar [30][31][32][33][34] to cylindrical [35][36][37]. At the experimental side, many authors have contributed to the study of water at hydrophobic interfaces using a wide variety of techniques such as scanning tunneling microscopy [38], environmental scanning electron microscopy and electron energy loss spectroscopy [39], ultrafast optical Kerr effect spectroscopy [40], atomic force spectroscopy [41], calorimetry [42], neutron diffraction [43][44][45][46] and electron cryomicroscopy [10].…”
Section: Introductionmentioning
confidence: 99%
“…29 Wilson et al 37 have already reviewed several aspects of premelting effects. They too noted that Dash and co-workers [38][39][40][41][42] discussed the presence of intergranular water and concluded that if the radius of curvature of the ice grains is 1 μm liquid water can be present down to ∼263 K. We also note that ice formed in nanopores of silica and other solids shows a melting endotherm that is broadened out on the low temperature side, [43][44][45] making it difficult to define the onset of bulk melting. The poorly defined onset temperature for melting of ice in 100% filled, 4 nm diameter pores of Vycor glass is ∼245 K (with a peak at 260 K) in Fig.…”
Section: B Thermal Conductivity Of the Hydrogel State Of Water Andmentioning
confidence: 99%